Intestinal Parasites Infection in AIDS Patients with Chronic Diarrhea at Dr. Soetomo General Hospital Surabaya - Prasetyo, R. Heru (Indonesian Journal of Tropical and Infectious Disease, 2010)
One of the mayor health problems among HIV-infected patients is opportunistic infection due to the defect of immunity. A cross sectional study was showed current the prevalence of intestinal parasites infection in AIDS patients with chronic diarrhea were being treated at Dr. Soetomo General Hospital Surabaya during the period June 2007 to May 2008. Fecal samples were collected from 122 AIDS patients with chronic diarrhea. Samples were examined for intestinal parasites using modified acid fast stain. Ninety-seven (79.5%) of the 122 were found to have intestinal parasitic infections, Entamoeba histolytica (61.5%; 75/122), Cryptosporidium (52.5%; 64/122), Giardia lamblia (5.73%; 7/122), and Trichuris trichiura (0,82%; 1/122). This study shows that parasitic infections are important clinical complications in AIDS patients in Surabaya Indonesia